Analisis Pengaruh Moderating Investment Opportunity Set dengan Kebijakan Dividend serta Moderating Investment Opportunity Set dengan Arus Kas Bebas terhadap Tingkat Leverage Perusahaan Makanan dan Minuman yang Terdaftar di BEI Periode 2003-2007 - Masruroh Masruroh; Tinjung Desy Nursanti; Lisa Lisa (Bina Nusantara University, 2011)
This research aims to examine whether there is any influence of investment opportunity set (IOS) on the affiliation between dividend policy and free cash flow to leverage enterprise-level. By using 42 samples of food and beverage companies listed on Indonesia Stock Exchange from 2003 to 2007, it is concluded that the dividend policy does not affect the company's leverage. However, the dividend policy together with investment opportunity set affect the level of corporate leverage. Free cash flow affects the level of corporate leverage. In the meantime, free cash flow to the investment opportunity set (IOS) also influences the level of corporate leverage, the dividend policy and free cash flow effect on the level of corporate leverage. Meanwhile, the dividend policy, free cash flow, investment opportunity set simultaneously affect the level of corporate leverage.